AN EXPERIMENTAL INVESTIGATION ON RADIANT FLOOR HEATING SYSTEMS AT VARIOUS OPERATING CONDITIONS - Karakoyun, Yakup; Acikgoz, Ozgen; Dalkilic, Ahmet Selim; Yumurtaci, Zehra (YILDIZ TECHNICAL UNIV, 2020)
In this study, heat transfer characteristics pertaining to a heated radiant floor are investigated experimentally. In order to achieve this aim, experiments have been conducted within extended supply water temperature ranging from 30 degrees C to 55 degrees C, and mass flow rate ranging from 0.056 kg/s to 0.125 kg/s according to experimental condition ranges in the relevant literature. Correlation comparison has been accomplished using a large number of experimental data including pioneer studies and international standards regarding with the determination of heat flux and heat transfer coefficients. Moreover, novel correlations providing convective, radiative and total heat fluxes have been derived, and it has been observed that most of the outcomes of correlations remain within deviation bands of +/- 15%, +/- 5% and +/- 20%, respectively. Apart from the literature, heat flux correlations corresponding to each heat transfer mechanisms are given and evaluated separately. Throughout experimental studies, the proportion of the radiative heat transfer to total one is found 60% approximately. Measured experimental data are given in the paper for other researchers validation problems on their theoretical and numerical works.
Keywords: Natural Convection; Enclosure; Radiant Heating; Floor Heating; Energy Saving; TRANSFER COEFFICIENTS; WALL; ROOM; PANEL; PERFORMANCE; CONVECTION; Thermodynamics